mtDNA D-loop sequence analysis of Kalang, Krayan, and Thale Noi buffaloes (Bubalus bubalis) in Indonesia and Thailand reveal genetic diversity - Suhardi, S.; Summpunn, P.; Wuthisuthimethavee, S. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
Kalang (KBuf), Krayan (KrBuf), and Thale Noi buffaloes (TBuf) are swamp buffalo genetic resources in Indonesia and Thailand. The maternally inherited mitochondrial DNA (mtDNA), particularly D-loop region is an important material for phylogenetic inference and analyzing genetic diversity. Therefore, the objectives of the present study were to evaluate genetic diversity and to reconstruct the phylogenetic tree within buffalo breeds in Kalimantan, Indonesia, and Phatthalung, Thailand using mtDNA D-loop sequences. A total of one hundred forty buffaloes (70 males and 70 females) were observed including 40 buffaloes from North (NK), 40 from East (EK), and 40 from South Kalimantan (SK) provinces Indonesia and 20 from Phatthalung (PT) province, Thailand. DNA samples were isolated from buffalo tail hairs. DNA sequences were manually assembled using BioEdit program with consideration of gaps and ambiguous sequences. The phylogenetic tree of buffalo was generated by PHYLIP software. The observed variables included haplotype diversity, genetic distance, and genetic tree. The 956 bp of amplified mtDNA D-loop fragment presented a total of 24 haplotypes with several mutations that included transitions (293), transversions (60), deletions (15), and insertions (20). The neighbor-joining tree using the Kimura 2 parameter model demonstrated two local buffalo clusters among buffalo from Kalimantan and Thailand with four buffalo relationship patterns observed from buffaloes in Kalimantan Island (KBuf and KrBuf), Indonesia. The Results of the present study demonstrated that the buffaloes sequence analysis revealed relatively high diversity and is a good basis to perform selection and modern buffalo breeding development.